Perancangan Game Edukasi Pengenalan Pakaian Adat Nusantara (CULTURZONE) Menggunakan Multimedia Development Life Cycle - Haris, Andi Fajrin; Wirya, Muhammad Nandar Cakra; Rahman, Baharuddin; Djafar, Imran; Kadang, Marsellus Oton; Arifin, Suci Ramadhani (Journal of Animation and Games Studies, 2024)
Archipelago traditional clothing is an inseparable part of Indonesian cultural identity. Each region has unique traditional clothing, reflecting the richness and diversity of cultures in Indonesia. By recognizing, studying and appreciating the traditional clothing of the Archipelago, we can strengthen Indonesia's cultural diversity, build a strong identity and promote our cultural heritage to the world. In order to introduce Indonesian traditional clothing to the younger generation, designing educational games can be an interesting and effective solution. This educational game is designed to provide an interactive experience for users in learning and getting to know various traditional clothes in Indonesia.